PERSPEKTIF DAN TANTANGAN PELAYANAN PRAKONSEPSI: STUDI KUALITATIF PADA BIDAN DAN PEMANGKU KEPENTINGAN DI KOTA BANDUNG - Kurniaty Ulfah; Ferina Ferina; Chris Sriyanti (Media Penelitian dan Pengembangan Kesehatan, 2025)
Indonesia continues to face major challenges in reducing maternal mortality, as many women begin pregnancy in poor health due to conditions such as anemia, hypertension, and chronic energy deficiency (CED). These health issues increase maternal risk and contribute to adverse birth outcomes like low birth weight and stunting. Although preconception care plays a crucial role in addressing these problems, it remains underutilized, particularly at the primary healthcare level. This study explored the perspectives and experiences of midwives and stakeholders regarding the challenges and strategies in delivering preconception care in Bandung City. A qualitative exploratory study was conducted from July to November 2024, involving in-depth interviews with 18 participants from two primary healthcare centers and the Bandung City Health Office. Data were analyzed thematically using Braun and Clarke’s approach, with triangulation through interviews, field observations, and member checking to ensure credibility. Two main themes emerged: midwives' views and experiences of preconception services, and stakeholders’ insights into implementation challenges. While midwives acknowledged the importance of preconception care in preventing complications, implementation was limited, hindered by the lack of operational policies, limited resources, low public awareness, and insufficient training. Stakeholders emphasized the need for community and family-based education, policy advocacy, and capacity strengthening of healthcare workers. In conclusion, preconception care has strong potential to prevent pregnancy complications and improve maternal and child health. Enhancing its impact within reproductive health services requires stronger policy backing, sufficient resource allocation, and integrated, sustainable implementation, including broader public education and ongoing health provider training.